Simulation of a parallel resonant inverter for electroheating applications; 6th Annual International Siberian Workshop and Tutorials on Electron Devices and Materials (EDM'2005), Erlagol, Altai - July 1-5, 2005 - Kozhemyak O. A. Olesya Anatolievna; Murkin M. N.; Zeman S. K.; Yaroslavtsev E. V. Evgeniy Vitalievich (2005, 2005)
Title screen